Molecular and seroepidemiologic studies of Enterovirus 71 infection in the State of Pará, Brazil Estudos soroepidemiológico e molecular de infecção por EV-71 no Estado do Pará, Brasil - Ceyla M.O. Castro; Ana Cecília R. Cruz; Edson E. da Silva; Maria de Lourdes C. Gomes (Revista do Instituto de Medicina Tropical de São Paulo, 2005)
In many countries, the Enterovirus 71 (EV-71) Picornaviridae family is associated to hand, foot and mouth disease in addition to acute neurological diseases while in Brazil these viruses are more closely associated to the latter group. The aim of this research was to use the first EV-71 isolate of the Northern region of Brazil in molecular and seroepidemiologic studies. Two (2.2%) out of 88 stool samples (44 cases of AFP), collected from January 1998 to December 2000 were positive for EV-71 isolation (73442/PA/99). Nucleotide sequence of the gen that codifies the VP1 protein showed that isolate 73442/PA/99 was similar to the EV-71 strains belonging to genotype B - more closely identified with EV-71 from North America. Neutralization test with 389 sera samples collected from January 1998 to November 2001, from individuals ranging from 0 to 15 years of age living in the city of Belém, State of Pará showed the following results in relation to isolate 73442/PA/99 and prototype BrCr: a total of 207 individuals (53.2%) had neutralization antibodies to both viruses, 167 (42.9%) had no antibodies and 15 showed the presence of neutralizing antibodies to one of the two viruses. Only 20.2% of the children aged 0 to 3 had neutralizing antibodies to EV-71, indicating that these children were more susceptible to the infection. Both the seroprevalence study and VP1 sequencing were important to demonstrate the spread and the molecular pattern of the EV-71 circulating in the Northern Region of Brazil. Em muitos países, o Enterovírus 71 (EV-71) família Picornaviridae é associado a doença de pé-mão e boca e doenças neurológicas agudas enquanto que no Brasil esse vírus está mais associado às últimas. O objetivo desta pesquisa foi utilizar em estudos moleculares e soroepidemiológicos, o primeiro isolamento de EV-71 obtido na região norte do Brasil. No período de janeiro de 1998 a dezembro de 2000 foram coletadas 88 amostras (44 casos de PFA) de fezes das quais, duas (2,2%) foram positivas para EV-71 (73442/PA/99). A seqüência de nucleotídeos do gen que codifica a proteína VP1 mostrou que o isolado 73442/PA/99 foi similar às cepas de EV-71 pertencentes ao grupo B- mais próxima das norte americanas. Teste de neutralização com 389 amostras de soro colhidas no período de janeiro de 1998 a novembro de 2001, de indivíduos com idade de 0 a 15 anos residentes na cidade de Belém, Estado do Pará mostrou os seguintes resultados em relação ao isolado 73442/PA/99 e ao protótipo BrCr: 207 indivíduos (53,2%) tinham anticorpos neutralizantes para ambos os vírus, 167 (42,9%) não tinham anticorpos e 15 tinham anticorpos para um dos dois vírus. Somente 20,2% das crianças com idade de 0 a 3 anos tinham anticorpos neutralizantes para EV-71, indicando que essas crianças estavam mais suscetíveis à infecção. Tanto o estudo de soroprevalência quanto o de sequenciamento da VP1 foram importantes para demonstrar a propagação e o padrão molecular do EV-71 circulante na região norte do Brasil.